2017
DOI: 10.1016/j.bbagen.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

IgG glycan patterns are associated with type 2 diabetes in independent European populations

Abstract: This work shows that IgG glycomic changes have biomarker potential and may yield important insights into pathophysiology of complex public health diseases, illustrated here for the first time in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
91
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 42 publications
19
91
1
Order By: Relevance
“…various large cohort studies using higher-resolution techniques a reduced fucosylation of diantennary structures in T2D and metabolic syndrome was found, notably, in Caucasians as well as Chinese and Ghanaian populations, even after adjustment for possible confounders including age, sex, and BMI [13,27,45]. Consistent results were reported for IgG fucosylation in the same, large T2D case-control cohort as presented here [46]. Increased branching/antennarity as well as sialylation of both di-and triantennary glycans were consistently reported by our and other groups (Fig.…”
Section: Association Of N-glycome With Type 2 Diabetessupporting
confidence: 88%
“…various large cohort studies using higher-resolution techniques a reduced fucosylation of diantennary structures in T2D and metabolic syndrome was found, notably, in Caucasians as well as Chinese and Ghanaian populations, even after adjustment for possible confounders including age, sex, and BMI [13,27,45]. Consistent results were reported for IgG fucosylation in the same, large T2D case-control cohort as presented here [46]. Increased branching/antennarity as well as sialylation of both di-and triantennary glycans were consistently reported by our and other groups (Fig.…”
Section: Association Of N-glycome With Type 2 Diabetessupporting
confidence: 88%
“…Our study of IgG N-glycosylation in type 2 diabetes has shown that a proinflammatory and biologically aged state is reflected on IgG N-glycan profiles [41]. In this study, decrease in galactosylation and sialylation of IgG was observed, as well as increase in IgG fucosylated structures with bisecting GlcNac and decrease in IgG fucosylated structures without bisecting GlcNac.…”
Section: Total Plasma Protein and Igg N-glycan Profiling In Type 2 DIsupporting
confidence: 56%
“…T ype 2 diabetes mellitus (T2DM) prevalence and its public health burden are rising worldwide in the 21st century. Genomic and other host factors, and their interactions with environment shape the risk for T2DM (Lemmers et al, 2017). The overall global prevalence of diabetes in adults between the ages of 20-79 years is reportedly 8.8% or 425 million adults who suffer from diabetes (International Diabetes Federation, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Glycosylation itself is regulated by complex systems including genetic and epigenetic factors (Kizuka and Taniguchi, 2016;Menni et al, 2013). For example, immunoglobulin G (IgG), a key effector of the humoral immune system with diverse roles in balancing inflammation at a system scale (Schwab and Nimmerjahn, 2013), displays changes in glycosylation in several diseases (Lauc et al, 2016), including T2DM (Adua et al, 2019;Keser et al, 2017b;Lemmers et al, 2017), and may possibly be involved in a mechanistic manner with diabetes in some situations (Tanigaki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation